Pediatric Obesity Etiology, Pathogenesis and Treatment (Contemporary Endocrinology,, 2018)
This second edition of Freemark's text embodies all of the strengths of the original work but is deeper and broader in scope, with new chapters on emerging themes including metabolomics, genomics, and the roles of gastrointestinal hormones, the microbiome, brown adipose tissue, and endocrine disruptors in the pathogenesis of childhood obesity. Reviews of the effects of weight excess on cognitive performance and immune function complement detailed analyses of the biochemical and molecular pathways controlling the development of childhood adiposity and metabolic disease. Critical assessments of nutritional interventions (including new chapters on infant feeding practices and vegetarian diets) and superb reviews of behavioral counseling, pharmacotherapy, and bariatric surgery provide practical guidance for the management of overweight children. Penetrating analyses of the obesity epidemic in its social, cultural, economic, and political contexts highlight challenges and opportunities for obesity prevention and community action. The perspective is international in scope and reflects the expertise and experience of many of the leading figures in the field. Comprehensive and up-to-date, this new edition of Pediatric Obesity: Etiology, Pathogenesis and Treatment will be an invaluable guide for all healthcare providers and policy makers concerned with the evaluation and care of children with nutritional and metabolic disease and with the societal implications of the obesity epidemic.